Analisis Kompetensi Profesional dan Sarana Prasarana Terhadap Kinerja Dosen Melalui Proses Pembelajaran Pada Sekolah Tinggi Ilmu Ekonomi Mah-Eisa Manokwari Propinsi Papua Barat - Maria Yertas (AkMen JURNAL ILMIAH, 2022)
This study aims to analyze the effect of professional competence and infrastructure on the performance of lecturers through the learning process at the Mah-Eisa Manokwari College of Economics. The research uses descriptive and verification methods with a quantitative approach. The population of this study were all lecturers of the Mah-Eisa Manokwari College of Economics totaling 100 people, the determination of the sample using the saturated technique, all populations were sampled so that the research sample was the same as the total population, namely 100 respondents. The results of the study indicate that: (1) Professional competence and infrastructure have a positive and significant effect on the learning process, (2) Professional competence and infrastructure have a positive and significant effect on lecturer performance (3) Professional competence and infrastructure. significant effect on the performance of lecturers through the learning process at the Mah-Eisa Manokwari School of Economics